Isokinetic Dynamometer Leg Extensor Peak Torque Measurement: A Time-Delayed Reliability and Score Selection Analysis Study - Brennan J. Thompson; Jennifer Xu (Journal of Functional Morphology and Kinesiology, 2023)
The reliability of isokinetic peak torque (PT) has been reported mostly using a short-term (<~10 day) inter-trial testing time frame. However, many studies and programs utilize a long-term (several weeks to months) inter-trial testing period. Additionally, the methods by which the PT value is selected and reported from a multiple rep testing scheme have not been well investigated for both reliability and PT absolute performance comparisons. The purpose of this study was to investigate the long-term reliability of isokinetic and isometric PT of the leg extensors with an emphasis on the differences among several PT score selection methods. Thirteen men and women (age = 19.5 years) underwent two testing trials separated by 28.8 (±1.8) days. Testing included maximal voluntary contractions of three sets of three reps for two isokinetic contraction conditions of 60 (Isok60) and 240 (Isok240) deg/s velocities, and three sets of one rep of isometric contractions for the leg extensors. The PT score was derived from seven different methods (see text for descriptions). Reliability as assessed from intraclass correlation coefficients (ICCs) varied widely across contraction conditions and PT score selection parameters. The Isok60 velocity overall had lower reliability (ICCs = 0.48–0.81) than Isok240 (0.77–0.87) across the conditions whereas the isometric PT variables showed moderate reliability (0.71–0.73). Overall the set 1 PT score selection parameters were generally lower (p ≤ 0.05) than those that involved sets two and three. Systematic error (p ≤ 0.05) was shown for 6 out of the 17 PT selection variables. On a subjective interpretation basis, when taking everything into account the best overall combination of time/trial efficiency, reliability, best/highest PT score parameter, and reduced risk of systematic bias appears to be the PT variable that uses the average of the highest two reps of the first two sets of three reps—i.e., averaging the highest two values of the six total reps from the first two sets.